Poor outcome in patients with diffuse large B-cell lymphoma is associated with high percentage of bcl-2 and Ki 67-positive tumor cells - Peruničić-Jovanović Maja; Jaković Ljubomir; Bogdanović Andrija; Marković Olivera; Čemerikić-Martinović Vesna; Mihaljević Biljana (Vojnosanitetski Pregled)
Background/Aim. Newly diagnosed patients with diffuse large B-cell lymphoma (DLBCL) tretaed with immunochemotherapy have durable remission and improved overall survival. It is important to identify high risk patients who may benefit from even more effective therapies. Methods. In a group of 50 newly diagnosed patients with DLBCL, treated with CHOP/R-CHOP (cyclophosphemide doxorubicine, vincristine, prednisone with or without rituximab) regimen, we analyzed the prognostic value of the expression of Ki67 and bcl-2 at diagnosis as well as other standard clinical parameters: International Prognostic Index (IPI), bulky disease, extranodal distribution and lactat dehydrogenase (LDH). Significance was tested according to response rate and overall survival. Results. Univariate survival analysis showed that high IPI had a statistically significant negative influence on overall and event free survival time (log rank, p < 0.01). The log rank test analysis signified that patients with a high proliferative fraction (Ki-67 > 60%) had a worse overall survival rate (OS5y) of 40% compared to those with low proliferation (Ki-67 < 60%) with OS5y of 80% (p < 0.01). There was a clear difference between bcl-2 positivity (treshold 50%) and the achievement of complete remission (66% vs 86% in patients with bcl-2 high and low levels respectively, p < 0.05). In survival analysis, patients with low bcl-2 expression had significantly higher OS5y - 68% compared to those with high bcl-2+ with OS5y 37% (p < 0.05). Multivariate analysis performed by Cox model revealed that IPI > 3, high Ki-67+, bcl-2 positivity had a significant independent prognostic value concerning overall survival (p < 0.05). Conclusion. An initial high IPI score associated with high Ki-67+ and bcl2+ could represent possible predictive factors of poor prognosis, which would help to identify a high risk subgroup of newly diagnosed DLBCL.